Multidisciplinary approaches to gliosarcoma: A case report and review of the literature - Collin M. Labak; Nicholas M. Rabah; Jasmine P. Kipke; Uma V. Mahajan; Kyle B. Labak; S. Ahmed Ali; Nicole Fowler; Andrew E. Sloan (Clinical Case Reports, 2022)
Abstract A 58‐year‐old right‐handed man presented to our tertiary care center with gliosarcoma (GS) infiltration through the dura, skull, and soft tissue. Patient had a previous history of right temporal GS, with four intracranial surgeries prior to presentation. A multidisciplinary approach was used to treat the lesion and perform reconstruction.